The role of T-helper and T regulatory cells in driving neutrophilic and eosinophilic inflammation in bronchiectasis - Fouka, Evangelia; Lindén, Anders; Bossios, Apostolos (Frontiers in Immunology, 2025)
Bronchiectasis is a chronic airway disease characterized by dysbiosis, persistent inflammation, and permanent structural airway damage. Neutrophilic inflammation is a key pathogenic feature, as indicated by enhanced neutrophil-derived proteases and formation of neutrophil extracellular traps (NETs), associated with poor prognosis. However, recent studies have identified an eosinophilic endotype in up to 30% of patients, characterized by higher levels of type 2 (T2) cytokines and fractional exhaled nitric oxide (FeNO). The role of T helper (Th) cells in the dysregulated inflammatory environment of bronchiectasis remains unclear. Evidence suggests that persistent bacterial infection can skew adaptive immunity from Th1 toward Th2 response, while the airway microbiome-IL-17 axis is also a critical regulator of chronic inflammation. T regulatory (Treg) cells have been shown to play a protective role against excessive chronic inflammation by modulating the function of several types of effector cells, including the Th17 subset. However, the capacity of this subset to delay or prevent disease progression remains to be determined Microbial dysbiosis, with loss of diversity and increased quantity of bacterial pathogens, may also be important for disease progression, and emerging evidence indicates that distinct inflammatory endotypes associate with specific microbiota alterations, especially in severe disease. In this review, we provide an overview of the immune cells and cytokine signaling that are involved in the pathogenesis of bronchiectasis. Additionally, we present the main endotypes of bronchiectasis and explore the relationships between the type of inflammation and alterations in microbiota, as well as the potential benefits of targeting specific pathophysiological mechanisms for the management of bronchiectasis. This review also examines how bacterial infection can shift adaptive immunity from Th1 toward Th2 responses, the role of the airway microbiome-IL-17 axis in chronic inflammation and the potential protective role of Treg cells against excessive inflammation. Novel therapeutic strategies are highlighted, with focus on targeting specific cytokine signaling pathways and restoring Th17/Treg balance These developments underscore a shift toward precision medicine in bronchiectasis, emphasizing the importance of identifying specific inflammatory endotypes to tailor treatment strategies effectively.